Stabilization of Expansive Soils Using Polypropylene Fiber - Sarah Adnan Hussein; Haifaa Abd Al-Rasool Ali (Salehan Institute of Higher Education, 2019)
Current research main aim is to study the effect of adding polypropylene fiber (PPF) on the behavior of expansive soil to reduce the swelling as percentage (0.5, 1 and 2%) of the weight of dry soil. Expansive soil used in this research was prepared artificially by mixing Ca-based bentonite from geological survey and mining company with sandy soil brought from Karbala city as percentage 80% bentonite to 20% sand of dry weight. Multiple laboratory tests have been carried are (Unconfined Compression Test, One-Dimensional Consolidation Test, Swelling Test, Sieve Analysis and Cycle Swell Shrink Test). A conventional odometer cell was modified to allow the study of swell- shrink cycle test to be carried out under controlled temperatures and surcharge pressure. The results showed that the increase in percentage of (PPF) led to decrease the swelling and to increase the unconfined compression strength. The wetting and drying results of (PPF) showed that with continuous cycles the effect of (PPF) keeps on reducing the swelling and the 2% of (PPF) produces less ratio of swell - shrink, which has obtained higher than 57 % in the improvement factor of swell and shrink.